Ta có: \(4xy\le\left(x+y\right)^2\)
Lại có: \(x;y>0\)
\(\Rightarrow\left(x+y\right)^2xy>0\)
\(\Rightarrow\frac{4xy}{\left(x+y\right)^2xy}\le\frac{\left(x+y\right)^2}{\left(x+y\right)^2xy}\)
\(\Rightarrow\frac{4}{\left(x+y\right)^2}\le\frac{1}{xy}\)
Ta có :
\(\left(x+y\right)^2-4xy\)
\(=x^2+2xy+y^2-4xy\)
\(=x^2-2xy+y^2\)
\(=\left(x-y\right)^2\ge0\)
\(\Rightarrow\left(x+y\right)^2\ge4xy\)
Lại có : \(x,y>0\)
\(\Rightarrow\frac{4}{\left(x+y\right)^2}\le\frac{4}{4xy}\)
\(\Rightarrow\frac{4}{\left(x+y\right)^2}\le\frac{1}{xy}\)<đpcm>